CLINICAL-NEUROPHYSIOLOGICAL AND NEUROIMMUNOLOGICAL CHARACTERISTICS OF CHRONIC HEADACHE FORMS - Akhmedova Dilafruz Bahodirovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Chronic  headache  disorders,  notably  chronic  migraine  and  tension-type headaches, represent a growing neurological concern due to their refractory nature and multidimensional  pathophysiology.  This  research,  grounded  on  a  cohort  of  315 patients, explores the interplay of neurophysiological and neuroimmunological factors, analyzing EEG markers, heart rate variability (HRV), and cytokine levels including IL-6, TNF-α, and IL-10. Our findings demonstrate distinct EEG profiles and elevated inflammatory markers in chronic migraine cases, supporting the hypothesis of central sensitization and immune dysregulation. Treatment optimization through multimodal approaches, tailored to patients’ neurobiological and psychological profiles, yielded significant reductions in attack frequency and improved quality of life.